Analysis of the Implementation of Customer Relationship Management (CRM) at PT. Milenial Agri Nusantara - Rizki, Alwi; Sujoko, Sujoko; Wening, Nur (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to analyze the implementation of Customer Relationship Management (CRM) at PT. Milenial Agri Nusantara. The company operates in the buying and selling of coffee beans for both domestic and international purposes. The research was conducted directly at PT. Millennial Agri Nusantara and the method used by the author to obtain respondents was through saturation sampling, which involves taking all available samples. The analysis in this research involves direct observation at PT. Milenial Agri Nusantara and interviews with respondents who are frequently involved in direct consumer interaction, namely the sales marketing team of PT. Millennial Agri Nusantara. Based on the observations and interviews, PT. Milenial Agri Nusantara applies Customer Relationship Management (CRM) using bonding, trust, empathy, and reciprocity methods, which can enhance customer loyalty. The implementation of Customer Relationship Management (CRM) can provide benefits for both the company and its customers, making it crucial for the company to maintain a good relationship with its customers.